Analysis of the Genduri Funeral Tradition from the Perspective of Maqashid al-Sharia - Lestari, Arum Windy; Elkhairati, Elkhairati (El-Rusyd, 2025)
The genduri funeral tradition represents a form of cultural heritage preservation aimed at offering prayers for deceased individuals through a series of rituals performed on specific days following death. This study seeks to identify the factors that sustain the continuity of this tradition and to analyze it from the perspective of maqashid al-sharia. The research employs a qualitative method with an ethnographic approach through observations, in-depth interviews, and document analysis to obtain a comprehensive understanding of the practices and cultural meanings underlying the genduri funeral tradition. The findings indicate that the tradition continues to be preserved because it is regarded as a hereditary custom and is supported by the belief that prayers offered by family members and the community benefit the deceased. From the perspective of maqashid al-sharia, the genduri tradition is permissible as long as it does not contain elements of shirk and embodies positive values such as strengthening social solidarity, enhancing spiritual awareness, and fostering interpersonal relationships. These findings suggest that local cultural practices can align with the objectives of Islamic law as long as they are carried out in accordance with the principles of aqidah and provide broad social benefits to the community.